The SAGE handbook of international social work. - Lyons, Karen, ....-; Hokenstad, Terry, ....-; Pawar, Manohar, ....- (Los Angeles : SAGE, 2012)
Social work is a profession that is increasingly involved with issues which have a global dimension. This Handbook tackles the global/local aspect of social work in its various forms and interrogates the key concerns that societies are facing through an international lens. The contributors show that, with an appreciation of commonalities and differences, local practices and appropriate forms of international activity can be better developed. Areas covered include: - Analysis of 'International social work' - Globalisation and indigenisation - Social justice and human rights - Poverty and livelihoods - Ecological issues - Migration - Education, theory, research and practice - Social work in different settings - Religion and spirituality - Responses to disasters and conflicts - Life course perspectives - Regional perspectives - Future directions With a truly international range of contributions, the Handbook incorporates perspectives from Asia, Africa, Europe, Australasia, the Middle East and the Americas. It will be an invaluable resource for undergraduates, postgraduates, researchers and academics working in the fields of social work, social welfare, human services, and community development worldwide, as well as service providers and policy makers in the international arena.
Keywords: Maatschappelijk werk